Tapentadol and Oxycodone/Naloxone Prescribing Patterns in Primary Health Care in Catalonia, Spain: A Cross-Sectional Study - Viñas-Bastart M; Oms-Arias M; Pedraza-Gutiérrez À; Lizano-Díez I; Mariño EL; Modamio P (Dove Medical Press, 2021)
Montserrat Viñas-Bastart,1 Míriam Oms-Arias,2 Àfrica Pedraza-Gutiérrez,2 Irene Lizano-Díez,1 Eduardo L Mariño,1 Pilar Modamio1 1Clinical Pharmacy and Pharmaceutical Care Unit, Department of Pharmacy and Pharmaceutical Technology, and Physical Chemistry, Faculty of Pharmacy and Food Sciences, University of Barcelona, Barcelona, Spain; 2Costa de Ponent Primary Care Directorate, Catalan Institute of Health, L'Hospitalet de Llobregat, Barcelona, SpainCorrespondence: Pilar ModamioClinical Pharmacy and Pharmaceutical Care Unit, Department of Pharmacy and Pharmaceutical Technology, and Physical Chemistry, Faculty of Pharmacy and Food Sciences, University of Barcelona, Av. Joan XXIII, 27-31, Barcelona, 08028, SpainTel/ Fax +34 934024544Email pmodamio@ub.eduObjective: To characterize the use of tapentadol and the combination oxycodone/naloxone in primary health care. Data on their use and possible misuse will allow the identification of risk factors and to design protocols to reduce and prevent avoidable harm to patients being treated for pain.Design: A descriptive, cross-sectional and multicenter study was performed.Setting: Fifty-three primary health care teams, which provides healthcare for 1,300,000 inhabitants.Patients: A total of 1840 patients had active prescriptions of tapentadol and 985 of oxycodone/naloxone.Methods: Demographic (age, sex) and clinical (glomerular filtration rate; active liver disease; dosing and duration of treatment), prescribed daily dose (according to age, sex, length of treatment), concomitant analgesic treatment and diagnosis. Patient information was obtained from medical records.Results: Most of the patients were women (> 74.0% in both cases), and the average age was 69.3 years (women: 70.1± 13.2; men: 66.7± 13.9 years) in the case of tapentadol and 70.6 years (women: 64.0± 13.6; men: 72.6± 14.3 years) in the case of oxycodone/naloxone. Only 12.2% of patients taking tapentadol and 12.1% taking oxycodone/naloxone had a normal renal function. In both cases, 4.1% of patients had active liver disease. The average length of treatment was 246.4 days in oxycodone/naloxone and 199.0 days in tapentadol. It was recorded that 85.1% of patients in the case of tapentadol and 89.0% in the oxycodone/naloxone had at least another drug prescribed for pain. About 42.2% of patients treated with tapentadol and 34.4% of patients treated with oxycodone/naloxone had associated neuralgia as a diagnosis.Conclusion: The pattern of use and profile of patients with tapentadol and oxycodone/naloxone had more similarities than differences, and suggested that prescribing practice, and monitoring should be assessed regularly to ensure patient safety and effective management of pain.Keywords: clinical practice pattern, chronic pain, opioids, oxycodone/naloxone, primary health care, culture, tapentadol